Food Habits and Human-jackal Interaction in Marwahi forest Division, Bilaspur Chhattisgarh - Akhtar, Naim; Chauhan, N. P. S. (Indian Forester, 2009)
Asiatic jackal (Canis aureus) is found to coexist with leopard and sloth bear in Marwahi Forest Division, Bilaspur (Chhattisgarh). Jackals were found to be omnivorous in this area; they consumed plant material, seeds and fruits. Jackals are creating considerable nuisance due to increasing biting cases to local people in Marwahi Forest Division. In total there were 220 cases of jackal attacks on people during 1998-2005. In Marwahi range, there were 181 cases of jackal attacks, whereas there were 12 and 27 cases of attacks in Gaurela and Pendra ranges respectively. Attacks on males (n=160) were more than females (n=60). No human death occurred so far due to jackal attack but rabies infection might be possible. Most of the jackal biting cases occurred in villages, followed by forests and crop fields. Marwahi range with less forest cover was found most affected (n=181) from jackal attacks. Occurrence of attack cases could be correlated with high jackal activity in human habitations for food requirement and movement of people in forest areas for collection of non-timber forest produce and grazing livestock. Recommendations for management of jackal population and mitigation of humanjackal conflict have been made.